Changes in Structure and Histochemistry of Glandular Trichomes of Thymus quinquecostatus Celak - Ping Jia; Ting Gao; Hua Xin (The Scientific World Journal)
The types, morphology, distribution, structure, and development process of the glandular trichomes on the leaves of Thymus quinquecostatus Celak had been investigated in this study. Two different types of glandular trichomes were determined in detail, namely, capitate trichomes and peltate ones. Besides, there were distinct differences on morphology, distribution, structure, and development process between the two kinds of trichomes. As the peltate trichome stepping into senium stage, it caved in the epidermis integrally, which was different from the capitate one. The secretion of the capitate trichome contained essential oil, polyphenols, and flavonoids, while, in addition to these three components, the secretion of the peltate one also contained acid polysaccharides. A distinctive difference was also seen in the secretory pathway of the secretion between the two types of trichomes. The secretion of capitate one was extruded through the cuticle of the head cell, but the secretion of the peltate one kept accumulating in the subcuticular space of the head cells until it was released by cuticle rupture.